A randomised controlled trial comparing two popliteal nerve catheter tip positions for postoperative analgesia after day‐case hallux valgus repair. (November 2016) - Ambrosoli, A. L.; Guzzetti, L.; Chiaranda, M.; Cuffari, S.; Gemma, M.; Cappelleri, G.
Summary: We compared the effect of two different positions of a sciatic nerve catheter within the popliteal fossa on local anaesthetic consumption and postoperative analgesia in patients undergoing day‐case hallux valgus repair. Eighty‐four patients were randomly allocated to receive a sciatic nerve catheter either between the tibial and peroneal components (sciatic group) or medial to the tibial nerve (tibial group). The primary endpoint was postoperative local anaesthetic consumption, while secondary endpoints were pain scores, number of occasions where sleep was disturbed by pain and incidence of insensate limb and foot drop at 24 h and 48 h postoperatively. Postoperative median (IQR [range]) local anaesthetic consumption was 126 (106–146 [98–180]) ml in the sciatic group versus 125 (114–158 [98–200]) ml in the tibial group (p = 0.103). Insensate limb occurred in 14 patients in the sciatic group versus one patient in the tibial group (p < 0.001), while foot drop was reported by six patients in the sciatic group and none in the tibial group (p = 0.012). Sciatic nerve catheter placement medial to the tibial nerve may be a superior analgesic technique for day‐case foot surgery.